If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x/3+2-x=3
We move all terms to the left:
2x/3+2-x-(3)=0
We add all the numbers together, and all the variables
-1x+2x/3-1=0
We multiply all the terms by the denominator
-1x*3+2x-1*3=0
We add all the numbers together, and all the variables
2x-1x*3-3=0
Wy multiply elements
2x-3x-3=0
We add all the numbers together, and all the variables
-1x-3=0
We move all terms containing x to the left, all other terms to the right
-x=3
x=3/-1
x=-3
| p3− 1=2 | | 2x+15=-2x-4 | | -5k+10=-k-14 | | 2x+40+4x+50=180 | | p/3− 1=2 | | Y+y+66=180 | | 6-0.75x=0.5x+1 | | x+14=5x+1 | | –7+3z=–2+4z | | 58+39+y=180 | | 2(7m)=-5 | | 3n-3=3n+3* | | 11x-13+8x+32=76 | | x²+3x+21=0 | | 7x+50)+40=300 | | 7x-12=40 | | 2/3d-10=-2 | | 0.35(x+4)=0.25(×-6) | | 1/4x+2/5x=10x-2 | | -5(x-3)^2=10 | | 18y+5=10y-61 | | 1x/4=22/4 | | 7x-12=4- | | 0.5y=27.2 | | (x+2)*4=13 | | 7(x-8)+3x=100 | | 7x+3x+10=-2(-5x+(5x)) | | 1/x+5/3x-5/6x+1=0 | | 12=2(x+2)-5(x+1) | | 3a+6-a=26-3a | | x+13=-3x+33 | | 2x+26=7 |